Ultrasound-guided low-volume anterior suprascapular nerve block for reduction of anterior shoulder dislocation in the emergency department: A case series - Chitta Ranjan Mohanty; Anju Gupta; Rakesh Vadakkethil Radhakrishnan; Neha Singh; Saroj Kumar Patra (Turkish Journal of Emergency Medicine)
Anterior shoulder dislocation (ASD) is the most common type of dislocation presented to the emergency department (ED) with severe pain and limitation of range of movement. Procedural sedation and analgesia are commonly used for ASD, but regional techniques are gaining popularity. Interscalene brachial plexus block is effective but has several limitations. Suprascapular nerve block (SSNB) has been explored for this indication. The SSNB is commonly performed using the posterior approach in a sitting position and can be technically difficult in dislocated patients. Recently, anterior subomohyoid approach performed in the lower neck has been described but has not yet been reported in the ED. We, hereby, report our experience of using low-volume ultrasound-guided anterior SSNB for procedural analgesia in 10 patients with ASD.